Deadly Companions: COVID-19 and Diabetes in Mexico. Issue 8 (16th November 2020) - Singer, Merrill
ABSTRACT: In this commentary, I assess the adverse syndemic interactions between COVID-19 and diabetes mellitus. This syndemic is of major concern for a country like Mexico which has seen a steady rise in the percentage of its population suffering these diseases. Mexico now has one of the highest rates of diabetes in the world and a rapidly growing COVID-19 caseload.